The Role of Emotional Intelligence as Moderation Between The Influence Forensic Accounting Investigation Audit On Behavior of Corruption - Yohanes Rusli; Yuli Asih; Daniel Wijaya (Universitas Agung Podomoro, 2023)
This study aims to examine the effect of forensic accounting on corrupt behavior and the influence of investigative audits on corrupt behavior. The Role of Emotional Intelligence as a moderator between the Influence of Forensic Accounting on Corrupt Behavior. The role of Emotional Intelligence as a moderator between the influence of Audit Investigation on Corrupt Behavior. By using multiple regression analysis. The researcher concludes that there is an effect of Forensic Accounting and Investigative Audit on Corrupt Behavior and the role of Emotional Intelligence as a moderator between the influence of Forensic Accounting and Investigative Audit on Corrupt Behavior